Pengaruh Latihan Model Bermain Terhadap Kemampuan Melempar Bola dalam Permainan Bocce pada Anak Tunagrahita - Isyani Isyani; Balkis NL. Esser (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2017)
This study aims to improve the ability to throw the ball in a bocce game on mind handicap children with a model exercise play. Population of this research is mind handicap children of Dharmawanita extraordinary school. The sample of the study amounted to 22 people taken using Purposive Sampling technique. The data analysis technique used in this research is Paired Sample t-test to see whether there is difference of average before and after by fulfilling requirement of parametric test descriptively and inferensially. From the results of the study it can be concluded that there is a significant influence of the practice of playing on the ability to throw the ball in a ball game bocce on mind handicap children. This is evidenced from the result of t-count obtained is 3.658 <1.71714 or 0.001 <α 0.05.